Detección de Neospora caninum en fetos bovinos abortados espontáneamente en el nordeste argentino - Lertora, W.J. (2010)
The aim of this work was to detect the presence of Neospora caninum in bovine neonates and bovine spontaneous abortions from Argentine northeast. Histopathological lesions compatible with neosporosis were found in 4 of 26 bovine spontaneous abortions (23 beef herds and 3 dairy herds). The Neospora caninum presence was confirmed with immunohistochemical analysis in encephalic tissue in 3 of 4 fetuses (2 beef herds and 1 dairy herd) that displayed microscopical lesions of neosporosis. Multifocal non-purulent encephalitis, myocarditis and hepatitis were the most relevant lesions. There were no lesions of neosporosis in 10 bovine neonates (8 beef herds and 2 dairy herds). This work confirms the presence of Neospora caninum in spontaneous bovine abortions of beef herds and dairy herds of the Argentine northeast. \n